2024 PRESIDENTIAL ELECTION AND STOCK PERFORMANCE: A COMPARATIVE STUDY BEFORE AND AFTER THE ELECTION - Hartadinata, Okta Sindhu; Farihah, Elva (Jurnal Magister Akuntansi Trisakti, 2025)
This study aims to provide empirical evidence regarding the impact of the 2024 presidential election on the reaction of the Indonesian stock market. Political events, such as elections, can significantly influence investor sentiment and market performance due to uncertainty regarding future economic policies. This study focuses on companies listed in the Kompas 100 Index on the Indonesia Stock Exchange (IDX), representing the most liquid and actively traded stocks. Using the event study method with a purposive sampling approach, this research selects 90 companies as the final sample. The findings reveal a significant difference in the average abnormal return before and after the voting day, suggesting that political stability and election outcomes influence investor confidence. These results provide valuable insights for investors in adjusting their investment strategies and for policymakers designing regulations to maintain economic and capital market stability. Understanding market reactions to elections can help stakeholders navigate risks and optimize financial decision-making.